Growth of the parvovirus minute virus of mice MVMp3 in EL4 lymphocytes is restricted after cell entry and before viral DNA amplification: cell-specific differences in virus uncoating in vitro. - Previsani, N (1997)
Two murine parvoviruses with genomic sequences differing only in 33 nucleotides (8 amino acids) in the region coding for the capsid proteins show different host cell specificities: MVMi grows in EL4 T lymphocytes and MVMp3 grows in A9 fibroblasts. In this study we compared the courses of infections with these two viruses in EL4 cells in order to investigate at which step(s) the infection process of MVMp3 is interrupted. The two viruses bound equally well to EL4 cells, and similar amounts of MVMi and MVMp3 input virion DNA appeared in the nuclear fractions of EL4 cells 1 h after infection. However, double-stranded replicative-form (RF) DNA of the two viruses appeared at different times, at 10 h postinfection with MVMi and at 24 h postinfection with MVMp3. The amount of MVMp3 RF DNA detected at 24 h was very small because it was produced only in a tiny subset of the population of EL4 cells that proved to be permissive for MVMp3. Replication of double-stranded viral DNA in EL4 cells was measured after transfection of purified RF DNA, cloned viral DNA, and cloned viral DNA with a mutation preventing synthesis of the capsid proteins. In each of these cases, DNA replication was comparable for MVMi and MVMp3. Production of virus particles also appeared to be similar after transfection of the two types of RF DNA into EL4 cells. Conversion of incoming 32P-labeled single-stranded MVM DNA to 32P-labeled double-stranded RF DNA was detected only after RF DNA amplification, indicating that few molecules serve as templates for viral DNA amplification. We showed that extracts of EL4 cells contain a factor which can destabilize MVMi virions but not MVMp3 by testing the sensitivity of viral DNA to DNase and by CsCl gradient analyses of viral particles. We therefore conclude that the MVMp3 life cycle is arrested after the transport of virions to the nucleus and prior to the replication of RF DNA, most likely at the stage of viral decapsidation.